2019
DOI: 10.1103/physreva.99.023416
|View full text |Cite
|
Sign up to set email alerts
|

Angularly resolved two-photon above-threshold ionization of helium

Abstract: Angularly resolved two-photon single ionization yields of helium resulting after the interaction with an ultrashort XUV pulse are obtained by numerically solving the full dimension time-dependent Schrödinger equation. The angular distributions reveal the underlying dominant mechanism, which depends on the effective photon energy absorbed and the pulse parameters. We specifically explore the contributions of radial and angular electron correlation terms. A single active electron picture is a qualitatively valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…the ground state, conventional anisotropy and asymmetry parameters fail to provide comprehensive tools for the analysis of photoionization from atomic superposition states. For example, the simplest case of a competition between one-and two-photon ionization processes can be analyzed using asymmetry parameters if the atom is prepared in the ground state [20][21][22][23][24][25][26][27] . In contrast, these analysis tools are either not applicable or do not provide a straightforward interpretation for the same processes if the atom is in the superposition of two states.…”
Section: Openmentioning
confidence: 99%
See 1 more Smart Citation
“…the ground state, conventional anisotropy and asymmetry parameters fail to provide comprehensive tools for the analysis of photoionization from atomic superposition states. For example, the simplest case of a competition between one-and two-photon ionization processes can be analyzed using asymmetry parameters if the atom is prepared in the ground state [20][21][22][23][24][25][26][27] . In contrast, these analysis tools are either not applicable or do not provide a straightforward interpretation for the same processes if the atom is in the superposition of two states.…”
Section: Openmentioning
confidence: 99%
“…Probing atoms and molecules in their ground or excited states with ultrashort laser pulses opens a new regime where several linear and nonlinear ionization pathways compete and interfere [20][21][22][23][24][25][26][27] . For example, it has been shown how the competition between resonant and nonresonant pathways depends on the pulse width 20 .…”
mentioning
confidence: 99%
“…From a theoretical point of view, the perturbative nonrelativistic framework has been employed in the calculations of total two-photon K -shell ionization cross section of many-electron systems in Refs. [12][13][14][15]. Further studies of TPI cross section have been conducted within the full relativistic framework for ionization of hydrogen-like atoms [16,17], and later for neutral atoms [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Nonresonant two-photon ionization can probe such correlation effects in both the initial and the final states of the target. A particularly sensitive observable is the photoelectron angular distribution (PAD), which can provide a detailed view of the underlying mechanisms involved in the photoionization process and its correlated nature, e.g., information on the role of continuum states and interchannel coupling [1][2][3][4][5][6][7][8][9][10][11][12]. The PAD emerges from a coherent summation over a set of final continuum states.…”
mentioning
confidence: 99%
“…Previous theoretical studies on angle-resolved two-photon ionization in helium have indicated that a single-activeelectron picture appears to be a valid approach in describing the photoionization dynamics for photon energies below the ionization threshold (and even in the above-threshold region) [1]. It is unlikely that this is true for more complex core targets.…”
mentioning
confidence: 99%